Effects of frequent assessments on the severity of suicidal thoughts: an ecological momentary assessment study - Chen, Tengwei; Niu, Lu; Zhu, Jiaxin; Hou, Xiaofei; Tao, Haojuan; Ma, Yarong; Silenzio, Vincent; Lin, Kangguang; Zhou, Liang (Frontiers in Public Health, 2024)
Objective In recent years, there has been a significant increase in research using ecological momentary assessment (EMA) to explore suicidal thoughts and behaviors (STBs). Meanwhile, concerns have been raised regarding the potential impacts of frequent and intense STBs assessments on the study participants. Methods From November 2021 to June 2023, a total of 83 adolescent and young adult outpatients (Mage = 21.0, SDage = 6.3, 71.1% female), who were diagnosed with mood disorders, were recruited from three psychiatric clinics in China. Smartphone-based EMA was used to measure suicidal thoughts three times per day at randomly selected times. We examined the change of suicidal thoughts in each measurement and within 1 day to evaluate potential adverse effects using Bayesian multilevel models. Results The 3,105 effective surveys were nested in 83 participants (median follow-up days: 14 days). The results of two-level models indicated that suicidal thoughts decreased during the monitoring period. However, this effect varied among different individuals in the two-level model. Conclusion Our findings did not support the notion that repeated assessment of suicidal thoughts is iatrogenic, but future research should continue to investigate the impact of frequent assessment on suicidal thoughts, taking into account individual differences and utilizing larger sample sizes.